Kinetics of the color difference and chroma in the thermal process pulp mango (Mangifera indica L.) Haden variety - Manayay, Damián (2013)
We have studied the kinetics of the color difference and chroma in the thermal process simple pulp (16 ° Brix) and concentrate (28 °Brix) Haden handle at different temperatures, the statistical variation of the colorimetric parameters L*, AE* and ∆C* with respect to time, and results in higher activation energy analysis of the effect of temperature on the kinetic constants, leading to the conclusion that correspond to reaction kinetics zero order.